2020
DOI: 10.15406/ijrrt.2020.07.00261
|View full text |Cite
|
Sign up to set email alerts
|

Impact of breast density on cancer detection: observations from digital mammography test sets

Abstract: Introduction: The aim of this study is to investigate the impact of breast density on the diagnostic efficacy of 273 breast screening radiologists reading 1 of 5 test sets of digital mammograms within the BREAST program. Methods: Retrospective data was collected from two hundred and seventy-three breast screening radiologists who participated in BREAST test sets between 2012 and 2017. Radiologists reviewed one of five test sets (labeled T1-T5) each containing 60 digital mammographic cases with 20 cancers and 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…This is supported by a previous study that found readers show significantly higher sensitivity rates in dense breasts when fewer dense breast cases are included in the dataset. 28 Second, these findings may not completely reflect the performance of this cohort of radiologists in actual screening practice because interval cancers were not considered. However, a previous study 29 comparing the performance of the same cohort of Australian radiologists in both clinical and test settings showed no difference in performance, suggesting that test set data can reasonably predict performance in a clinical setting.…”
Section: Discussionmentioning
confidence: 92%
“…This is supported by a previous study that found readers show significantly higher sensitivity rates in dense breasts when fewer dense breast cases are included in the dataset. 28 Second, these findings may not completely reflect the performance of this cohort of radiologists in actual screening practice because interval cancers were not considered. However, a previous study 29 comparing the performance of the same cohort of Australian radiologists in both clinical and test settings showed no difference in performance, suggesting that test set data can reasonably predict performance in a clinical setting.…”
Section: Discussionmentioning
confidence: 92%